What is spirituality? - K. Waaijman (Acta Theologica)
This essay provides, first of all, a historical perspective on the nature of spirituality by investigating its early forms, followed by a discussion of two approaches in the last century. It then investigates three basic forms of spirituality, concluding with an overview of elements of spirituality.